PENANAMAN SPIRITUAL REMAJA KARANG TARUNA MELALUI PENGKAJIAN KITAB HIKAM DI DESA KARANGREJO KECAMATAN GEMPOL PASURUAN - Zainal Fanani; Ahmad Ma'ruf (Universitas Yudharta Pasuruan, 2019)
Karang Taruna's spiritual planting approach through the study of the Hikam book in Karangrejo Village, Gempol Subdistrict was carried out and guided directly by the leaders and caretakers of the Taklim Assembly in ways of humanism preaching such as Walisango using several approaches including; experience, which means providing a spiritual experience with the concept of the experience of the salaf cleric, habituation which means caretakers of the taklim assemblies provide istiqomah learning by slowly leading the youth Karang Taruna, emotional which means changing negative emotional overflowing in youth Karang Taruna carried out in the past then those who have been trapped in a negative environment become close to their god, rational, which means giving knowledge to the youth of Karang Taruna proportionally that is acceptable with reason so that it is easily practiced, functional which means that al-Hikam's learning can produce results and later teaching can be implemented in the youth of Karang Taruna and the last form of exemplary which means giving a factual example to the youth of Karang Taruna with the object of good behavior giving a model in the form of their capacity.